THE EFFECT OF ORGANIC FERTILIZER AND NITROPOSKA ON GROWTH AND YIELD OF PEANUT ON ULTISOL SOIL - Ansi, Azhar (Universitas Halu Oleo, 2024)
The aim of the research was to study the effect of organic fertilizer and Nitrophoska on the growth and yield of peanuts on ultisol soils. The study was conducted in the Labibia sub district, Kendari city, from January to April 2023. The study was arranged in a randomized block design (RAK) in a factorial pattern with three replications consisting of 2 factors. The first factor was organic fertilizer which consisted of 4 levels, namely: control (B0), 5 t ha-1 (B1), 10 t ha-1 (B2), and 15 t ha-1 (B3). The second factor was Nitrophoska fertilizer which consisted of 3 levels, namely control (P0), 75 kg ha-1 (P1), and 150 kg ha-1 (P2) so that there were 4x3x3=36 experimental units. Observation variables included: plant height, leaf area, weight of 100 seeds, yield per plot and yield per ha. The results showed that there was an interaction between organic fertilizer and Nitrophoska on the observed variables. The best results were obtained in the treatment of 15 t ha-1 of organic fertilizer and 150 kg ha-1 of Nitrophoska fertilizer with the highest production reaching 0.93 t ha-1.